Ampholytic ion-exchange magnetic beads: a promising tool for selecting short fragments in circulating cell-free DNA analysis - He, Gan; Wang, Weixuan; Zhou, Yongxia; Zhao, Guowei; Liao, Juan (Frontiers in Oncology, 2024)
Objective For liquid biopsy of cancer, the extraction of circulating cell-free DNA (cfDNA) from plasma is required. We evaluated the efficacy of use of magnetic submicron particles coated with abundant small zwitterions (MSP-ZEWBs) for extracting short fragments of cfDNA. Methods We developed and optimized an MSP-ZEWB-based cfDNA extraction method using ampholytic ion-exchange materials and compared its results with those using a control kit. We measured the cfDNA concentration by quantitative polymerase-chain-reaction and using the Qubit method and analyzed cfDNA fragmentation patterns using a bioanalyzer. Results The fragment size of cfDNA isolated from glycine hydrochloric acid at a pH of 2.2 exhibited a better alignment with the DNA marker. The highest DNA intensity was observed at the final concentration of 0.8% polyethylene glycol 8000. The intensity of cfDNA decreased significantly when isolated from plasma with DNA marker using MSP-ZEWBs with an adsorption buffer containing guanidine hydrochloride or isothiocyanoguanidine. All fragments were successfully extracted using MSP-ZEWBs from both plasma and phosphate-buffered saline. Notably, the intensity of short cfDNA fragments isolated using MSP-ZEWBs remained consistent for recovery of long DNA fragments. indicating a potential selective of small fragments. Conclusion The extraction of plasma cfDNA with MSP-ZEWBs requires no protein denaturation, shows resistance to cells remaining in plasma, and demonstrates higher overall efficiency and better reproducibility than other extraction methods. Use of MSP-ZEWBs may greatly enhance liquid biopsy of cancers through the analysis of plasma cfDNA in clinical practice.